Image Based Fake Indian Coin Detection - Swathi, K; Mohanan, K. P (International Journal of Computer Sciences and Engineering, 2018)
Nowadays, illegal counterfeit coins are considerably affecting the financial transactions in society. This work proposes an efficient image based fake coin detection, which can be applied to ensure the authenticity of coins. Although several types of fake currency detectors are already existing, fake coin detection still remains as a challenging problem. Image based approach have benefits in terms of cost and ease of usage. The fake coin detection uses a vector space approach, termed as dissimilarity space. It is a vector space constructed by measuring the dissimilarity between the coin image and the prototype. Dissimilarity between the coin images is obtained using the combination of Difference Of Gaussian (DOG) detector and Scale Invariant Feature Transform (SIFT). The proposed system adapts to coin rotation and scaling. In this work, one class learning method is used, so for training the classifier, only genuine Indian coins are needed.